1969
DOI: 10.1084/jem.129.5.993
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anti-Lymphocyte Globulin on Cell-Mediated Resistance to Infection

Abstract: Mice which survive infection with Listeria monocytogenes are highly resistant to reinfection and specifically hypersensitive to Listeria antigens (1). The resistance and the accompanying state of delayed-type hypersensitivity can both be transferred to normal recipients with immune lymphoid ceils obtained from actively infected donors (2). Since neither of these immunological modalities can be transferred with immune serum (1, 2, 3), it is a useful model for studying the action of anti-lymphocyte globulin on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 11 publications
1
42
0
Order By: Relevance
“…Tile absence of antimacrophage activity in U.A.M.L.S. which has been demonstrated in both the present and other studies (Mackaness and Hill, 1969;Gotjamanos and Gill. 1970) excludes such a pos.sibility in the case of antilymphocytic antibody.…”
Section: The Activity Of Cytophilic Antibody In the Localization Of Isupporting
confidence: 57%
“…Tile absence of antimacrophage activity in U.A.M.L.S. which has been demonstrated in both the present and other studies (Mackaness and Hill, 1969;Gotjamanos and Gill. 1970) excludes such a pos.sibility in the case of antilymphocytic antibody.…”
Section: The Activity Of Cytophilic Antibody In the Localization Of Isupporting
confidence: 57%
“…Mackaness and colleagues have shown that the lymphocytes responsible for Listeria resistance are sensitive to anti-lymphocyte serum (13), appear in the thoracic duct early after stimulation, do not recirculate from blood to lymph (14), and tend to accumulate in sites of specific or nonspecific inflammation (15). These results may be characteristics of T lymphocytes which m~y show functional heterogeneity during their life-span.…”
Section: Discussionmentioning
confidence: 89%
“…Immunity to both Mycobacterium tuberculosis (15,16) and Listeria monocytogenes (17,18) has been shown to be T cell-dependent, and interestingly, another abscess producing organism, Staphylococcus aureus, has also been shown to elicit delayed hypersensitivity in mice (19). The effector mechanism by which T cell-dependent immunity against B. fragilis-induced abscesses operates has yet to be defined.…”
Section: With F Varium Plus Enterococcus Resulted In Abscesses Scessmentioning
confidence: 99%